INTEGRATING TECHNOLOGY TO ENHANCE GRAMMAR LEARNING AMONG DIPLOMA STUDENTS - Sulaiman, Fazillah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the effectiveness of integrating technology in grammar classes for diploma students. The objectives of the study are to examine the efficacy of selected technological tools in teaching grammar, to assess students’ engagement and attitudes toward technology-assisted grammar learning and to evaluate the students’ improvement in grammar performance through digital tools. With a class of 25 learners from UiTM Melaka, digital tools such as Grammarly, Kahoot!, and Google Classroom were utilised to improve engagement, accuracy, and self-editing skills. The findings suggest that incorporating technology enhances student motivation, participation, and understanding of grammar rules, demonstrating its potential as a supportive pedagogical tool in tertiary education.